Evaluation of the Passivation Effects of PEDOT:PSS on Inverted Perovskite Solar Cells - Qi, Yifang; Almtiri, Mohammed; Giri, Hari; Jha, Surabhi; Ma, Guorong; Shaik, Abdul Kalam; Zhang, Qiqi; Pradhan, Nihar; Gu, Xiaodan; Hammer, Nathan I.; Patton, Derek; Scott, Colleen; et al. (Advanced energy materials, 2022)
Poly(3,4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is a popular hole transport material in perovskite solar cells (PSCs). However, the devices with PEDOT:PSS exhibit large open‐circuit voltage (Voc) loss and low efficiency, which is attributed to mismatched energy level alignment and the poor interface of PEDOT:PSS and perovskite. Here, three polymer analogues to polyaniline (PANI), PANI–carbazole (P1), PANI–phenoxazine (P2), and PANI–phenothiazine (P3) are designed with different energy levels to modify the interface between PEDOT:PSS and the perovskite layer and improve the device performance. The effects of the polymers on the device performance are demonstrated by evaluating the work function adjustment, perovskite growth control, and interface modification in MAPbI3‐based PSCs. Low bandgap Sn–Pb‐based PSCs are also fabricated to confirm the effects of the polymers. Three effects are evaluated through the comparison study of PEDOT:PSS‐based organic solar cells and MAPbI3 PSCs based on the PEDOT:PSS modified by P1, P2, and P3. The order of contribution for the three effects is work function adjustment > surface modification > perovskite growth control. MAPbI3 PSCs modified with P2 exhibit a high Voc of 1.13 V and a high‐power conversion efficiency of 21.06%. This work provides the fundamental understanding of the interface passivation effects for PEDOT:PSS‐based optoelectronic devices. Three polymer analogues to polyaniline (PANI), PANI–carbazole (P1), PANI–phenoxazine (P2), and PANI–phenothiazine (P3) are designed with different energy levels to modify the interface between poly(3,4‐ethylenedioxythiophene):poly(styrene sulfonate) and the MAPbI3‐based perovskite layer and improve the device performance. The order of contribution for the three effects of the polymer modification is work function adjustment > surface modification > perovskite growth control.